How Social Media Impacts on Customer Brand Engagement, Brand Trust and Brand Loyalty - Khusniah, Riza; Siti Astuti, Endang; Wilopo (FIA UB, 2024)
This research analyzes the effect of Social Media Marketing Activities, Customer Brand Engagement, and Brand Trust on Brand Loyalty. Currently, coffee drinks and activities have become a trend for the community. Starbucks, the world's largest coffee shop company, was born with a luxurious image. By demographic class, the Starbucks customer segment is middle to upper class, classified as a masstige brand. The masstige brand position is between the upper mid-level and super premium courses. Business competition for masstige brands is more sophisticated and global, which expedites adapting communication technology to build brand loyalty. Social media marketing activities reinforce brand loyalty through customer engagement to improve customer relations. Even the transfer of information between brands to customers through social media has the potential to boost brand trust. The research method used is quantitative. This research questionnaire was distributed online to 210 customers of the masstige brand Starbucks in three major cities in East Java Province. The data were analyzed using PLS. This study's results show that the 5 hypotheses significantly affect the dependent variable. It indicates that implementing Social Media Marketing Activities, CBE, and BT strategies can improve BL on customers of masstige brand Starbucks.